Integration of Rice Prices at Producer, Wholesaler, and Urban and Rural Consumer Markets with Paddy Prices at the Farm Gate - Makbul, Yogi; Ratnaningtyas, Sudrajati; Pradono, Pradono (Archives of Business Research, 2019)
In this study, we analyzed the integration of rice prices at the producer, wholesaler, and urban and rural consumer markets with paddy prices at the farm gate, which has important implications for rice pricing policy. A high price policy can lead to high paddy prices, and thereby increase the profits of paddy farms. Although this policy can generally ensure food security, it may have the effect of decreasing rice consumption. A high-price rice policy can, nevertheless, be beneficial if rice prices are sufficiently well integrated with paddy prices, which can simultaneously enhance paddy farm profits and ensure domestic food security. For the purposes of this study, we examined monthly price data obtained from the Central Bureau of Statistics of Indonesia for the period from January 2013 to December 2016. Using this data, we applied an error correction model (ECM) to integrate the rice prices at the producer, wholesaler, and urban and rural consumer markets with paddy prices at the farm gate. The results showed that producer, wholesaler, and rural consumer market rice prices were significantly integrated with paddy prices at the farm gate. Moreover, if necessary, the government can intervene in these markets to stabilize paddy prices to maintain food security.